Towards the implementations of coordinated cadastral system in Malaysia : large cadastral network adjustments - Abd. Majid A. Kadir; Shahrum Ses; Chia, Wee Tong; Teng, Chee Boo; JUPEM (1999 : Pulau Pinang) (Skudai : Universiti Teknologi Malaysia, 1999)
27